Drug-induced cardiac arrest: a pharmacovigilance study from 2004–2024 based on FAERS database - Gaocan Ren; Gaocan Ren; Pingping Huang; Pingping Huang; Jinhui Zhang; Jin Liu; Zian Yan; Xiaochang Ma; Xiaochang Ma; Xiaochang Ma (Frontiers in Cardiovascular Medicine)
ObjectiveUtilizing the FDA Adverse Event Reporting System (FAERS) database, this study conducts signal detection for drugs associated with cardiac arrest (CA), aiming to optimize clinical decision-making and ensure safer drug usage.MethodsAdverse event reports related to CA from the first quarter of 2004 to the second quarter of 2024 were extracted from the FAERS database. Signal detection was conducted using the reporting odds ratio (ROR) and proportional reporting ratio (PRR) to identify drugs associated with an increased risk of CA.ResultsA total of 66,431 reports were analyzed, comprising 34,508 males (51.9%) and 31,923 females (48.1%). The majority of cases (71.8%) were reported by healthcare professionals, with adults (≥18 years old) representing the predominant group. Clinical outcomes showed that 67.2% of cases resulted in death. Out of 82 drugs with over 100 CA-related reports, 43 displayed positive signals. The top five drugs identified by ROR were: carisoprodol [ROR (95% CI): 34.13 (29.62–39.32)], sugammadex [ROR (95% CI): 26.93 (22.56–32.16)], regadenoson [ROR (95% CI): 20.00 (17.69–22.60)], alprazolam [ROR (95% CI): 12.82 (12.19–13.48)], and propofol [ROR (95% CI): 11.93 (10.61–13.41)]. In the system drug signal detection, musculo-skeletal system drugs ranked highest [ROR (95% CI): 30.99 (27.74–34.62)], followed by alimentary tract and metabolism drugs [ROR (95% CI): 4.75 (4.59–4.92)], nervous system drugs [ROR (95% CI): 4.51 (4.4–4.61)], anti-infective drugs [ROR (95% CI): 4.13 (3.74–4.57)], cardiovascular drugs [ROR (95% CI): 3.89 (3.78–4.01)], and antineoplastic and immunomodulating agents [ROR (95% CI): 2.16 (2.13–2.2)].ConclusionThis study identifies over 40 drugs potentially associated with an elevated risk of CA based on FAERS data. Healthcare professionals should be particularly vigilant when prescribing these drugs, especially to patients with a history of heart disease, and ensure rigorous monitoring of their cardiac health.